Question #05dd5 Calculus Basic Differentiation Rules Summary of Differentiation Rules 1 Answer Ratnesh Bhosale Mar 11, 2017 a=3 Explanation: f(x)= (ax^2-1)(3+2x) f(x)= 3ax^2+2ax^3-3-2x f(x)= 2ax^3+3ax^2 -2x-3 By Differentiating, f'(x) = 6ax^2 +6ax-2 Put x=1 f'(1) = 12a-2 34 = 12a-2 12a = 36 a=3 Answer link Related questions What is a summary of Differentiation Rules? What are the first three derivatives of (xcos(x)-sin(x))/(x^2)? How do you find the derivative of (e^(2x) - e^(-2x))/(e^(2x) + e^(-2x))? How do I find the derivative of y= x arctan (2x) - (ln (1+4x^2))/4? How do you find the derivative of y = s/3 + 5s? What is the second derivative of (f * g)(x) if f and g are functions such that f'(x)=g(x)... How do you calculate the derivative for g(t)= 7/sqrtt? Can you use a calculator to differentiate f(x) = 3x^2 + 12? What is the derivative of ln(x)+ 3 ln(x) + 5/7x +(2/x)? How do you find the formula for the derivative of 1/x? See all questions in Summary of Differentiation Rules Impact of this question 1616 views around the world You can reuse this answer Creative Commons License